PREPARATION OF LEAD MAGNESIUM NIOBATE-LEAD ZIRCONATE TITANATE FILMS AND THEIR CRYSTALLIZATION BEHAVIORS - Silvester Tursiloadi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2002)
PREPARATION OF LEAD MAGNESIUM NIOBATE-LEAD ZIRCONATE TITANATE FILMS AND THEIR CRYSTALLIZATION BEHAVIORS. The thin films with composition near morpotropic phase boundary (MPB) of the system xPb(Mg1/3, Nb2/3)O3-yPbTiO3-zPbZrO3 (x = 0 – 0.35, y = 0.47 and z = 0.53), were prepared by sol-gel method. The starting materials were consisted of Pb(iso-OC3H7)2, Zr(n-OC4H9)4, Ti(iso-OC3H7)4, Mg(CH3COO)2 4H2O and Nb(OC2H5)5. The 1-propanol was used as solvent. The concentration of PMN-PT-PZ in coating solution was 0.7 M, and the pH of the solution was 4.5. The thin films were prepared by dipcoating and spincoating. The crystallization behaviors of the PMN-PT-PZ thin films showed that the formation of perovskite phase at low temperature becomes difficult with increasing the content of PMN. The amounts of pyrochlore and perovskite phase in PMN-PT-PZ films depended on the heating temperatures, and PMN contents. Single-phase perovskite was found for the coated films containing 0 and 12.5 mol% after calcinating at 600 oC, 21 mol% after calcinating at 700oC, and 30 mol% after calcinating at 750oC. Single-phase perovskite of coated films will never be found when the content of PMN was 35 mol%.